HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KEJADIAN STUNTING PADA BALITA DI DESA PARUNGSEHAH KECAMATAN SUKABUMI - Faizal Azmi; Alinda Alinda; Ega Yusanti; Siti Alisa Meilia; Gina Nurul Sakinah; Ria Rosmala; Andi Lesmana (Jurnal Sosio dan Humaniora (SOMA), 2023)
Stunting is a chronic malnutrition problem that occurs during a critical period in growth and development, starting in the fetus. This nutritional problem means that the quality of life of children in terms of growth and development does not match their genetic abilities. Poor growth in babies is caused by underdevelopment. Stunting is a stunting disease in children which is characterized by short stature. Stunting can be caused by several factors, including infection or malnutrition in pregnant women, malnutrition in infancy, and an unfavorable environment. The purpose of this study is to provide guidelines for preventing stunting in early childhood to the people of Parungseah Village, Sukabumi Regency, and it is hoped that parents will be aware of the importance of knowledge about stunting from an early age. We specifically encourage health workers in this setting to provide health education to increase mothers' knowledge about stunting.